Atopic dermatitis, mucosal atopy and house dust allergens. Allergological and clinical observations in a group of atopic patients. - Schiera, A.; Beneggi, M.; Fiocca, A.; Galbiati, G. (European Journal of Pediatric Dermatology, 2018)
In the present study we considered the possible relationship between delayed cutaneous hypersensitivity against purified extracts of dermatophagoides and other clinical and serologic data, in a group of young atopic subjects with both cutaneous and mucosal diseases. In addition, we also studied these patients' response to commercial house dust mite allergen preparations, different for concentration and composition of antigens. We studied two groups of patients (aged 3-18 years), each one composed of ten subjects with atopic diseases. There were seven female patients and therteen male patients. The first group (group A) was composed of ten subjects with a history of allergic diseases (bronchial asthma, rhinitis) and with positive prick test and RAST for house dust mites. The second group (group B), was composed of ten subjects with atopic dermatitis (sometimes associated with respiratory atopy). Patch test were performed with two different solutions containing the whole purified bodies of Dermatophagoides pteronyssinus (D. pt.) 10% and Dermatophagoides farinae (D. far.) 10%, compared with a mixture of the whole purified bodies of both D. pt. and D. far. 20%. Our study showed a high percentage of positive responses to patch testing with house dust mite antigens in atopic subjects, both in patients affected by atopic dermatitis and in those with respiratory atopy. Furthermore, we obtained a larger number of positive patch test reactions with the preparation containing the mixture of D. pt. and D. far. 20%.